THE PAN-AFRICAN IDEAL UNDER A NEW LENS: THABO MBEKI'S CONTRIBUTION (The Strategic Review for Southern Africa, 2020)
This essay is an attempt to assess the important evolution undergone by the pan-African ideology. It argues that from its inception the ideal was marked by moral values and political ambitions that were grounded on the desire to reverse the dominant views of African inferiority. This has not resolved the identity and racial connotations that have provoked the proliferation of views about what pan-Africanism really means. Yet pan-Africanism has become the most powerful magnet for generations, and remains the most solid reference for the construction of an integrated Africa. The last 10 years have witnessed large-scale affirmation of a particular brand of the pan-African ideology. Thabo Mbeki is one of the most significant architects of this development.